Effect of Different Nutrient Management on the Yield and Economics of Kharif Sunflower (Helianthus annuus L.) - Soumya, B.; Suryavanshi, V. P.; Karanjikar, P. N.; Sireesha, P.; Ghungarde, S. N. (International Journal of Economic Plants, 2025)
A field experiment was carried out during kharif season (June–September, 2023), at Experimental Farm of Agronomy Section, College of Agriculture, Latur, Maharashtra, India to assess the yield and economic of kharif sunflower (Helianthus annuus L.) under different nutrient management. The experiment was laid out in Randomized Block Design (RBD) with seven treatments replicated thrice. The treatments were T1-RDF (80:40:40 kg NPK ha-1), T2-RDF+FYM 5 t ha-1, T3-RDF+Multimicronutrient Grade-I @ 25 kg ha-1, T4-RDF+FYM 5 t ha-1+Multimicronutrient Grade-I @ 25 kg ha-1, T5-RDF+Spraying of Multimicronutrient Grade-II @ 0.2% at 25 DAS and 45 DAS, T6-RDF+FYM 5 t ha-1+Spraying of Multimicronutrient Grade-II @ 0.2% at 25 DAS and 45 DAS and T7-Control. The results showed that the application of RDF+FYM 5 t ha-1+Multimicronutrient Grade-I @25 kg ha-1 (T4) recorded maximum Plant height (198.85 cm), Number of functional plant-1(35.04), Head diameter plant-1 (20.21 cm), Weight of head plant-1 (92.76 g), Number of filled seeds plant-1 (1074), Total number of seeds plant-1 (1237), Seed yield plant-1 (73.65 g), yield (1942 Kg ha-1), biological yield (7187 Kg ha-1), GMR (Rs. 131279 ha-1), and NMR (Rs. 81740 ha-1) being at par with RDF+Multimicronutrient Grade-I @ 25 kg ha-1 (T3) and RDF+Spraying of Multimicronutrient Grade-II @ 0.2% at 25 DAS and 45 DAS (T6) and found significantly superior over rest of the treatments. The highest B:C ratio (2.65) was recorded with the application of RDF+FYM 5 t ha-1+Multimicronitrient Grade-I @ 25 kg ha-1 (T4).